Hambatan dan Solusi dalam Evaluasi Program SMK Pusat Unggulan Pada SMK Negeri di Kota Balikpapan - Murdariyanto, I Gusti Bagus Didie; Komariyah, Laili; Haryaka, Usfandi (Universitas Pakuan, 2025)
BARRIERS AND SOLUTIONS IN THE EVALUATION OF THE SMK CENTRE OF EXCELLENCE PROGRAMME AT PUBLIC SMK IN BALIKPAPAN CITY The purpose of this research is to find out the inhibiting factors as well as the solution to overcome the inhibiting factors of SMK Centre of Excellence programme at SMK Negeri Kota Balikpapan. This research uses qualitative approach with data collection through interview, observation, and documents. The results show that the programme is able to improve the competence of graduates to match the needs of the business world and the industrial world. However, there are still some obstacles, such as the lack of co-operation with the industry, limited school facilities, and the lack of curriculum alignment with industry needs. To overcome this, improvement steps are needed such as strengthening relationships with industry, improving school facilities, and aligning the curriculum with industry needs. With these steps, it is hoped that the programme can run better and help graduates become more work-ready.